COMPARATIVE ANALYSIS OF CONSUMER PREFERENCES BETWEEN INTERNATIONAL OVER LOCAL BRAND IN MANADO (CASE STUDY ON EVERBEST AND BUCCHERI) - Lumintang, Yecika Glady; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: For customers, brand means familiarity and credibility as they get to experience some contacts in their everyday life; therefore, they use the brands as an indicator to try or making decision to buy new product. Consumers especially in developing countries have certain expectations from the brands and tend to rely on brand as indicator to purchase by default. The shoes industry is one of the markets that consumers are facing various choices of international and local brand and these products are seen to be popular for consumers. The aim of this research is to analyze consumer preferences between International over Local brand in Manado measure by durability, country of origin, price, and style. This research is quantitative type of research, which uses primary data obtained through questionnaires and uses independent sample t-test as the analytical tool. The population of this research is peoples in Manado who has experience in Everbest and Buccheri brands, where the sample size is taken from 100 respondents who also has experience with both brands. The result from this research found that there is no significant difference between Everbest and Buccheri brands measured by durability, country of origin, price, and style. Everbest and Bucccheri should more considering on the factors that influence the consumer buying behavior.Keywords: comparative analysis, consumer preferences, shoes, international and local brand, everbest and buccheri.